1998
DOI: 10.1111/j.1440-1746.1998.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal damage induced by compound 48/80: Roles of serotonin and nitric oxide

Abstract: The roles of nitric oxide (NO) and serotonin (5-HT) in the development of gastric mucosal lesions induced by compound 48/80 (48/80) were investigated in rats. Repeated i.p. administration of 48/80 (1 mg/kg) produced damage in the stomach with severe oedema in the submucosa. The lesions induced by 48/80 were prevented by FPL-52694 (a mast cell stabilizer) and methysergide but not tripelennamine. The lesions were also inhibited by simultaneous administration of N(G)-monomethyl-L-arginine (L-NMMA), and this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…As opposed to this, a delay in gastric emptying and a reduction of food intake was observed after administration of the ghrelin receptor antagonist [10] . The possibility that nonspecific effects of [ D -Lys 3 ]-GHRP-6 leading to gastroprotection had masked ulcerogenic effects related to ghrelin receptor blockade cannot be excluded; in line with this, a recent study [46] ]-GHRP-6 has to be excluded, since, if present, it would have resulted in ulcerogenic rather than protective activity [47] .…”
Section: Discussionmentioning
confidence: 96%
“…As opposed to this, a delay in gastric emptying and a reduction of food intake was observed after administration of the ghrelin receptor antagonist [10] . The possibility that nonspecific effects of [ D -Lys 3 ]-GHRP-6 leading to gastroprotection had masked ulcerogenic effects related to ghrelin receptor blockade cannot be excluded; in line with this, a recent study [46] ]-GHRP-6 has to be excluded, since, if present, it would have resulted in ulcerogenic rather than protective activity [47] .…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have demonstrated the involvement of iNOSgenerated NO in gastric damage induced by chemical substances, such as serotonin or compound 48/80 [16,17], by stress [18] or by Helicobacter pylori infection [19]. However, the role of iNOS in NSAID-induced gastric damage has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it seems unlikely that ebselen administered to rats treated once with compound 48 /80 at the stage of gastric mucosal lesion formation exerts a protective effect against the lesion progression by inhibiting gastric acid secretion. Yasuhiro et al (36,37) have suggested that endogenous nitric oxide (NO) produced by inducible nitric oxide synthase (iNOS) increasing in gastric mucosal tissues, in addition to enhanced gastric mucosal lipid peroxidation and released endogenous serotonin, is involved in the pathogenesis of gastric mucosal lesions induced by repeated treatment with compound 48 /80 in rats. The authors have also suggested that the deleterious role of NO during compound 48 /80 treatment may be accounted for by a cytotoxic action of peroxynitrite, which is formed in the presence of NO and superoxide radical (36, 37).…”
Section: Discussionmentioning
confidence: 99%